From Being to Love: Reconceiving the Trinity in Light of Jean-Luc Marion's Phenomenological Shift - Russell, Heidi (Horizons, 2014)
This article uses the work of Jean-Luc Marion, emphasizing his shift from Being to Love as an analogue for God, to make a parallel shift from Person to Love in Trinitarian theology, thereby addressing some of the issues raised by the social trinitarians. The article then focuses on the work of Catherine Mowry LaCugna as particularly congruent with the shift suggested by Marion, but adds to LaCugna's work a conception of the immanent Trinity that is grounded in Marion's phenomenological shift. Conceiving of God as the unoriginate source of Love that is revealed in Word and enacted in Spirit allows one to understand personhood and community, not in and through the relationships between the Trinitarian Persons, but in and through Love incarnate in the human person of Jesus Christ, and Love enacted in the Spirit present in the community, forming it into the Body of Christ.